2018
DOI: 10.3233/jpd-181485
|View full text |Cite
|
Sign up to set email alerts
|

Repairing the Brain: Gene Therapy

Abstract: In vivo gene therapy for neurodegenerative disorders has turned out to be a formidable challenge. It is a field not much older than twenty years, but we were many who would have predicted a much easier path towards the clinic using this treatment modality. For Parkinson's disease patients, this has meant a frustrating wait, seeing many promising therapies being forgotten after a few pre-clinical proof-of-concept studies. The reasons for this are both scientific and economical. However, this is slowly but surel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Previously commented limiting factors, along with the need to use appropriate vehicles that are able to deliver efficiently the genetic material, justify the hard path of brain gene therapy to reach clinical practice. In fact, although many phase I clinical trials have been reported; only a few have reached phase II [154]. However, with the new emerging technologies applied to gene therapy, the cure of brain diseases might look like a reasonable option in the near future [155].…”
Section: General Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously commented limiting factors, along with the need to use appropriate vehicles that are able to deliver efficiently the genetic material, justify the hard path of brain gene therapy to reach clinical practice. In fact, although many phase I clinical trials have been reported; only a few have reached phase II [154]. However, with the new emerging technologies applied to gene therapy, the cure of brain diseases might look like a reasonable option in the near future [155].…”
Section: General Conceptsmentioning
confidence: 99%
“…However, with the new emerging technologies applied to gene therapy, the cure of brain diseases might look like a reasonable option in the near future [155]. One of the most promising approaches is to explore the use of non-viral vectors as gene delivery systems due to their safer profile, easy production capacity, and lower cost when compared to their viral vector counterparts [154].…”
Section: General Conceptsmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 , 7 Today, viral gene therapy with a variety of viruses is used in oncology, vaccination, and many other disciplines in clinical science. 8 , 9 , 10 , 11 Gene therapy vectors have been used preclinically for host genome editing and clinically for the expression of intracellular proteins, surface receptor presentation, and/or the secretion of therapeutics. 12 , 13 , 14 , 15 Recently, multiple gene delivery vectors have been developed in the expanding field of cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy is a fast-growing field of biomedical research, recently exceeding more than 4000 ongoing or completed clinical trials . This rapid progress became possible due to successes in numerous DNA delivery methods, including physical gene transfer, synthetic nanoparticles, and viral or cellular vectors. , Especially for in vivo applications, viral vectors have been shown to achieve high transduction rates and sustained expression. Adenoviral vectors (AdVs) in particular are among the most frequently applied gene vectors, and they are currently being investigated for multiple clinical applications, including but not limited to the fields of vaccines, oncology, or rare diseases. , Among the more than 100 human adenovirus serotypes, the most prominent and best studied AdV serotype is the human adenovirus serotype C5 (HAdV-C5). , …”
mentioning
confidence: 99%